The art of being indispensable at work : win influence, beat overcommitment, and get the right things done - Tulgan, Bruce (Boston Harvard Business Review Press, 2020)
"What's the secret to being indispensable--being a true go-to person--in today's workplace? With new technology, flatter organizations, far-flung virtual teams, and constant change, getting things done at work is tougher and more complex than ever. We're in the midst of a collaboration revolution--but sometimes it feels more like a meltdown. Managers and executives are trying harder than ever to keep up and stay effective, relying on cross-functional coordination, better planning and resource sharing, simplified processes, and speeded-up work. It's a herculean challenge, and people are struggling. Overcommitment grows and burnout looms. But even amid the seeming chaos of the matrix organization--where you are constantly being asked to do things by people who aren't your boss, and where you must ask things of others who don't report to you--there is always that special person who seems indispensable, who seems to thrive on complexity, and who is able to stay focused and positive and get the right things done: This is the go-to person. In this game-changing yet practical book, talent guru and bestselling author Bruce Tulgan reveals the secrets of the go-to person in our new world of work. Based on an intensive study of people at all levels, in all kinds of organizations, Tulgan shows how go-to people not only behave differently, but also think differently, basing their decisions and actions on their own personal influence rather than on any formal designation of authority. At the heart of the go-to person's unique credo are the basics of "the ask" and the response--a powerful reimagining of how to say yes and when to say no. Nearly a century ago, Dale Carnegie's classic How to Win Friends and Influence People propelled millions of readers up the ladder of success. Now, in a world of work where you truly need to interact with everybody, Tulgan provides the new must-read guidebook for achieving real influence and learning to thrive when the guardrails of traditional management are pulled away"--
Includes index.
Keywords: Executives; Success in business; Influence (Psychology); Industrial management; Burn out (Psychology)